A Rapid Review of the Reporting and Characteristics of Instruments Measuring Satisfaction with Reference Service in Academic Libraries - Senior, Heidi; Ward, Tori (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – The objective of this review was to examine research instrument characteristics, and to examine the validity and reliability of research instruments developed by practicing librarians, which measure the construct of patron satisfaction with academic library reference services. The authors were also interested in the extent to which instruments could be reusedMethods – Authors searched three major library and information science databases: Library and Information Science Technology Abstracts (LISTA); Library Science Database (LD); and Library Literature & Information Science Index. Other databases searched were Current Nursing and Allied Health Literature (CINAHL); Education Resources Information Center (ERIC); Google Scholar; PubMed; and Web of Science. The authors identified studies of patron satisfaction with academic library reference services in which the researcher(s) developed an instrument to study the satisfaction construct. In this rapid-review study, the studies were from 2015 and 2016 only. All retrieved studies were examined for evidence of validity and reliability as primary indicators of instrument quality, and data was extracted for country of study, research design, mode of reference service, data collection method, types of questions, number of items related to satisfaction, and content of items representing the satisfaction construct. Instrument reusability was also determined.Results – At the end of the screening stage of the review, a total of 29 instruments were examined. Nearly all studies were quantitative or mixed quantitative/qualitative in design. Twenty-six (90%) of the studies employed surveys alone to gather data. Twelve publications (41%) included a discussion of any type of validity; five (17%) included discussion of any type of reliability. Three articles (10%) demonstrated more than one type of validity evidence. Nine articles (31%) included the instrument in full in an appendix, and eight instruments (28%) were not appended but were described adequately so as to be reusable. Conclusions – This review identified a range of quality in librarians’ research instruments for evaluating satisfaction with reference services. We encourage librarians to perform similar reviews to locate the highest-quality instrument on which to model their own, thereby increasing the rigor of Library and Information Science (LIS) research in general. This study shows that even a two-year rapid review is sufficient to locate a large quantity of research instruments to assist librarians in developing instruments.